Crystal structures of ASK1‐inhibtor complexes provide a platform for structure‐based drug design. (3rd July 2013) - Singh, Onkar; Shillings, Anthony; Craggs, Peter; Wall, Ian; Rowland, Paul; Skarzynski, Tadeusz; Hobbs, Clare I.; Hardwick, Phil; Tanner, Rob; Blunt, Michelle; Witty, David R.; Smith, Kathrine J.
Abstract: ASK1, a member of the MAPK Kinase Kinase family of proteins has been shown to play a key role in cancer, neurodegeneration and cardiovascular diseases and is emerging as a possible drug target. Here we describe a 'replacement‐soaking' method that has enabled the high‐throughput X‐ray structure determination of ASK1/ligand complexes. Comparison of the X‐ray structures of five ASK1/ligand complexes from 3 different chemotypes illustrates that the ASK1 ATP binding site is able to accommodate a range of chemical diversity and different binding modes. The replacement‐soaking system is also able to tolerate some protein flexibility. This crystal system provides a robust platform for ASK1/ligand structure determination and future structure based drug design.